The 4C's of PAL – An evidence-based model for implementing peer assisted learning for mature students. Issue 3 (4th May 2023) - Bermingham, Nevan; Boylan, Frances; Ryan, Barry
ABSTRACT: Peer Assisted Leaning (PAL) programmes have been shown to enhance learner confidence and have an overall positive effect on learner comprehension, particularly in subjects traditionally perceived as difficult. This research describes the findings of a three-cycle Action Research study into the perceived benefits of implementing such a programme for mature students enrolled on a computer science programming module on an Access Foundation Programme in an Irish University. The findings from this study suggest that peer learning programmes offer students a valued support structure that aids transition and acculturation into tertiary education whilst simultaneously improving their subject-matter comprehension and confidence. An evidence-based model of PAL implementation for mature students was subsequently developed, underpinned by the associated pedagogic theory and the findings of the study. Our model promotes a student-focused peer educational enhancement framework that is transferable into the wider higher education setting.